Developing a systematic approach to evaluate and predict building service life - Chen, Chien-Jung; Juan, Yi-Kai; Hsu, Yin-Hao (Journal of Civil Engineering and Management, 2017)
Analyzing the reasonable service life of buildings is a critical step to evaluate the decision for building utilization, reuse, or disposal. If buildings manifest service value, sustainable refurbishment and reuse methods can be employed to extend their service life. Previous studies on building service life largely focused on physical obsolescence. Few studies have analyzed other aspects. The objective of the present study was to propose a systematic approach to evaluate and predict the reasonable service life of buildings. First, the Fuzzy-Delphi Method (FDM) and analytical hierarchy process (AHP) were adopted to determine the final evaluation criteria and weights. Second, a mathematical model for predicting building service life was developed by combining the evaluation criteria, six obsolescence factors, and diagnostic scores. Finally, the model was applied to four case studies. The results produced by the model were consistent with those determined by an expert panel, verifying its effectiveness as a tool for decision making for formulating favorable suggestions concerning asset disposal, urban renewal, and renovation. Later obsolescence of buildings can be reduced by taking into account the proposed obsolescence criteria in the construction of new buildings to avoid implementing designs that are prone to obsolescence, thereby enhancing building service life.